Organizational Justice as a Key Driver of Organizational Citizenship Behavior in the Banking Industry - Fauzan Muttaqien; Zohaib Hassan Sain (Business and Applied Management Journal, 2026)
This study examines the effects of distributive, procedural, and interactional justice on organizational citizenship behavior (OCB), with workplace spirituality serving as a mediating variable within the banking sector. The research is based on how multidimensional organizational justice influences OCB through workplace spirituality especially in highly structured and performance-oriented industries such as banking. This study employed a quantitative research approach involving 126 banking employees in East Java, Indonesia. Data were collected using a structured questionnaire distributed through a convenience sampling technique and analyzed using SEM-PLS with SmartPLS 4.0. The findings indicate that distributive justice significantly affects OCB (β = 0.255; p < 0.05) and workplace spirituality (β = 0.285; p < 0.05). In contrast, procedural justice (β = 0.096; p > 0.05) and interactional justice (β = 0.073; p > 0.05) do not demonstrate significant direct effects on OCB. However, procedural justice (β = 0.334; p < 0.05) and interactional justice (β = 0.337; p < 0.05) significantly influence workplace spirituality, while workplace spirituality significantly enhances OCB (β = 0.642; p < 0.001). Workplace spirituality significantly mediates the relationships between distributive justice, procedural justice, interactional justice, and OCB. The findings contribute to the organizational justice literature by demonstrating that workplace spirituality serves as an important psychological mechanism through which perceptions of justice translate into positive discretionary behavior among banking employees.